Pengaruh Model Numbered Head Together Terhadap Hasil Belajar Siswa Pada Pembelajaran Pendidikan Agama Islam - Nurfauziah, Nabilla; Hermawan, Iwan; Aini Farida, Nur (STAI Ihyaul Ulum Gresik, 2024)
The lack of application of a fun learning model can cause students to feel bored when learning in class, and can affect student learning outcomes in the subject of Islamic Religious Education. Therefore it is necessary to apply learning models, one of which is by using the Numbered Head Together model. Numbered Head Together is a cooperative model that involves students playing an active role in learning. This study aims to find out whether there is an influence of the Numbered Head Together learning model on student learning outcomes in PAI learning in class VII SMPN 1 Lemahabang Karawang.The method used in this research is Quasi Experimental with Non Equivalent Control Group Design type. The sample in this study amounted to 84 students consisting of 42 students of class VII H for the experimental group and 42 students of class VII I for the control group. The data collection technique used in this study is a test. Based on testing the hypothesis with the independent sample t-test Ha is accepted with the results obtained 0.004 ˂ 0.05 . It can be concluded that there is an influence of the Numbered Head Together learning model on student learning outcomes in class VII PAI learning at SMPN 1 Lemahabang Karawang.